SYSTEM OF FORMATION OF LEGAL CULTURE AMONG STUDENTS OF HIGHER EDUCATION INSTITUTION - N. I. Gafurova (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes the role of legal consciousness and culture in the development of society, the main tasks of developing the legal culture of students, and gives practical suggestions and recommendations for the development of legal culture of students.